Solar energy applications - Rao, K. R. 1933- (ASME Press, 2020)
"Renewable Energy has emerged as an important source for energy and power generation from renewable resources, naturally replenished on a human timescale, such as sunlight, wind, rain, hydro including tides and waves, geothermal heat, and from traditional and modern biomass. Worldwide investments in renewable energy are surpassing expectations, significantly in Europe (Germany and Spain), the US, in Asia (China and India) and in Australia. Energy, and Power Generation Handbook: Established and Emerging Technologies, edited by K.R. Rao, and published by ASME Press in 2011 was a comprehensive reference work of 32 chapters authored by 53 expert contributors from around the world, with the authors drawn from different specialties, each an expert in the respective field and with several decades of professional expertise and scores of technical publications. Recognizing the need of treating Renewable Energy and Power Generation as a separate field ASME Press initiated "Renewable Energy Series" to address each entity of Renewable Energy in a separate book, revising pertinent chapters of the 2011 Handbook and bringing the coverage up-to-date"--